How liver pathologies contribute to T1rho contrast require more careful studies - Wáng, Yì Xiáng J.; Chen, Weitian; Deng, Min (Quantitative Imaging in Medicine and Surgery, 2017)
Liver T1rho has been proposed as an imaging biomarker for liver fibrosis (1-5). In the recent study of Xie et al. (6,7), 18 healthy subjects, 18 patients with fatty liver, and 18 patients with liver fibrosis had T1rho MR imaging performed. The diagnosis of liver fibrosis was based on serologic evidence of hepatitis B or C virus infection and liver stiffness criteria by ultrasonic elastography. Mean liver T1rho values in fibrotic group (52.6±6.8 ms) were significantly higher than those of healthy subjects (44.9±2.8 ms, P